Graft of the NT-3 persistent delivery gelatin sponge scaffold promotes axon regeneration, attenuates inflammation, and induces cell migration in rat and canine with spinal cord injury. (March 2016) - Li, Ge; Che, Ming-Tian; Zhang, Ke; Qin, Li-Na; Zhang, Yu-Ting; Chen, Rui-Qiang; Rong, Li-Min; Liu, Shu; Ding, Ying; Shen, Hui-Yong; Long, Si-Mei; Wu, Jin-Lang; et al.
Abstract: Persistent neurotrophic factor delivery is crucial to create a microenvironment for cell survival and nerve regeneration in spinal cord injury (SCI). This study aimed to develop a NT-3/fibroin coated gelatin sponge scaffold (NF-GS) as a novel controlled artificial release therapy for SCI. In vitro, bone marrow-derived mesenchymal stem cells (MSCs) were planted into the NF-GS and release test showed that NF-GS was capable to generate a sustainable NT-3 release up to 28 days. MSCs in NF-GS had high cell activity with excellent cell distribution and phenotype. Then, the NF-GS was transplanted into the injury site of spinal cord of rat and canine in vivo, which exhibited strong biocompatibility during post-transplantation period. Four weeks following transplantation, the concentration of NT-3 was much higher than that in control groups. Cavity areas in the injury/graft site were significantly reduced due to tissue regeneration and axonal extensions associated with myelin sheath through the glial scar into the NF-GS. Additionally, the NF-GS decreased the inflammation by reducing the CD68 positive cells and TNF-α. A striking feature was the occurrence of some cells and myelin-like structure that appeared to traverse the NF-GS. The present results demonstrate that the NF-GS has the property to control the release of NT-3 from the NT-3/fibroin complex thus facilitating regeneration of injured spinal cord.